2023
DOI: 10.1136/bmjopen-2023-072736
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous catheter drainage versus percutaneous needle aspiration for liver abscess: a systematic review, meta-analysis and trial sequential analysis

Abstract: ObjectiveTo compare the effectiveness and safety of percutaneous catheter drainage (PCD) against percutaneous needle aspiration (PNA) for liver abscess.DesignSystematic review, meta-analysis and trial sequential analysis.Data sourcesPubMed, Web of Science, Cochrane Library, Embase, Airiti Library and ClinicalTrials.gov were searched from their inception up to 16 March 2022.Eligibility criteriaRandomised controlled trials that compared PCD to PNA for liver abscess were considered eligible, without restriction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to Losie et al, the absence of drainage is associated with an increased 30-day mortality in PLA (univariate OR 5.8, 95% CI 1.58–21.30, p = 0.006) 34 . Regarding the optimal procedure, a recent meta-analysis concluded that catheter drainage is superior to needle aspiration in terms of treatment success and duration of antibiotic therapy, especially for large PLA (diameter > 6 cm or abscess volume > 113 mL) 25 . A German multicenter study identified a low complication rate of < 2% in 6,420 image-guided catheter drainages of the liver 51 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Losie et al, the absence of drainage is associated with an increased 30-day mortality in PLA (univariate OR 5.8, 95% CI 1.58–21.30, p = 0.006) 34 . Regarding the optimal procedure, a recent meta-analysis concluded that catheter drainage is superior to needle aspiration in terms of treatment success and duration of antibiotic therapy, especially for large PLA (diameter > 6 cm or abscess volume > 113 mL) 25 . A German multicenter study identified a low complication rate of < 2% in 6,420 image-guided catheter drainages of the liver 51 .…”
Section: Discussionmentioning
confidence: 99%